Internationalization of Higher Education: some reflections on Russia and China - Morgan, W. John; Guilherme, Alexandre Anselmo (Educação, 2017)
Given that there appears to be a dichotomy within the BRICS, we focus on Russia and China, discussing recent developments in their respective Higher Educational systems, and what these changes might mean in terms of internationalization. Moreover, given that the importance of Higher Education for a balanced development is something that is now widely recognised by International Organizations, such as the World Bank and UNESCO, as well as by governments, we enquire if past and current changes in Russian and Chinese Higher Educational systems have encouraged balanced development in those countries. ***A internacionalização do Educação Superior: algumas reflexões sobre a Rússia e China*** Dado que parece haver uma dicotomia entre os países que compoe os BRICS, nos concentramos na Rússia e na China, discutindo os desenvolvimentos recentes em seus respectivos sistemas de Educação Superior e o que essas mudanças podem significar em termos de internacionalização. Além disso, uma vez que a importância do Ensino Superior para um desenvolvimento equilibrado é algo agora amplamente reconhecido por Organizações Internacionais, como o Banco Mundial e a UNESCO, bem como por governos, investigamos se mudanças passadas e atuais no sistema Russo e Chinês de Educação Superior incentivaram o desenvolvimento equilibrado nesses países.